Three essays on public policies in Indonesia - Tampubolon, Devanand Pandapotan, author; Pena, Anita Alves, advisor; Braunstein, Elissa, committee member; Cutler, Harvey, committee member; Seidl, Andrew, committee member (Colorado State University. Libraries, 2023)
This dissertation studies tax burden, tax compliance, and cooking fuel choice and energy policy in Indonesia. The three papers observe the impact of recent public policy changes in taxation and cooking fuel. The first paper comprehensively analyzes the burden of Value-Added Tax (VAT), focusing on current exemptions. This paper uses expenditure as the proxy of income or welfare to examine the VAT burden. This paper finds that the effective VAT rate is 4.51 percent nationally and weakly progressive. The effective VAT rate is relatively similar to other developing countries, but only half of the developed countries. The VAT burden is lower and more progressive in rural areas than in urban areas. The tax burden on food consumption is lower and regressive, while higher and progressive for nonfood consumption. While households in non-Java islands spend more than households in Java, this paper finds that the effective tax rate in non-Java is less than in Java. The first paper also simulates the impact of the VAT reform implemented in April 2022. The result shows that if the exempted items are maintained (by only changing nontaxable to taxable but still excused from VAT) and the tax rate increase from 10 percent to 11 percent, the tax burden will increase proportionally to all expenditure deciles by 10 percent. However, the calculations suggest that if all exemptions are excluded, the tax burden will be double that of the previous tax regime and the poorest households will get hit more than the richest. The second paper studies the impact of the high VAT threshold introduced in 2014 on small firms' reported revenues. The threshold is set to help both the tax authorities and small businesses. However, the existence of a threshold will be counterproductive in its strength of providing transaction information. Due to a lack of trading information, the tax authority will have more difficulties assessing the tax obligation owed by the taxpayers. This paper utilizes quasi-natural experiments and Difference-in Difference regression to explore the treatment effect. The treatment group is wholesale firms, and the control group is retail firms. This paper finds that wholesale reports lower revenues by 58-70 percent for four years than those in the retail sectors. This paper also finds that the decrease in reported revenues is larger than the reported costs. This may lead us to conclude that the lower reported revenues are due to underreporting revenues. The third paper studies the determinants of cooking fuel choices and energy policy in Indonesia amid the zero kerosene program. This study finds that government policy is important for the transition to clean energy. One percent increase in the distribution of LPG Kits increases the probability of clean energy usage by 2%. The impact is almost double in urban areas compared to rural areas. All socioeconomic and demographic factors significantly influence the household choice of cooking fuel. Households with higher income and wealth, better house infrastructure, formal education, electric network, and mobile phone are more likely to be clean energy users. On the other hand, working women, household heads working in agriculture, and bigger household sizes are identic to unclean energy. The age and gender of the head have different effects on urban and rural households. In line with the findings of previous studies, household income is still the main determinant of clean energy. One percent increase in income will impact the probability of clean energy by 10 to 13 percentage points. With steady GDP growth of around 5-6% yearly, Indonesia has a good path to transition to clean energy. The three essays complement each other to strengthen Indonesia's economic development. Taxation is essential for adequate and sustainable public funding and clean energy is for better living and productivity. Chapter One provides insight into estimates of the VAT burden in society. This will help the government to improve VAT revenue with a less negative impact on society, especially for low-income people. Chapter Two provides insight for government to improve the utilization of information from the VAT system and tax compliance. Adequate and sustainable self-funding through taxation will enable the government to provide sustainable clean cooking fuel, which may help society become healthier and more productive. Chapter Three has the implication that tax policy can be used to promote clean cooking fuel. The current VAT exemption on households that use electric power up to 6600 VA should be maintained to encourage low-income families to use clean cooking fuel.
Keywords: cooking fuel; tax burden; value-added tax; registration threshold; clean energy; tax compliance